2017
DOI: 10.3390/ma10080972
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for High-Performance, Solution-Processed, Amorphous ZrO2 Gate Insulator TFT with a High Concentration Precursor

Abstract: Solution-processed high-k dielectric TFTs attract much attention since they cost relatively little and have a simple fabrication process. However, it is still a challenge to reduce the leakage of the current density of solution-processed dielectric TFTs. Here, a simple solution method is presented towards enhanced performance of ZrO2 films by intentionally increasing the concentration of precursor. The ZrO2 films not only exhibit a low leakage current density of 10−6 A/cm2 at 10 V and a breakdown field of 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The result measured by XRD showed that the ZrO 2 has already crystallized and the corresponding crystallization peaks were shown in Figure 8a [22]. That was the main reason why ZrO 2 was easier to break down.…”
Section: Resultsmentioning
confidence: 99%
“…The result measured by XRD showed that the ZrO 2 has already crystallized and the corresponding crystallization peaks were shown in Figure 8a [22]. That was the main reason why ZrO 2 was easier to break down.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we could increase the HRS by approximately 10 times due to the decreased current leakage. The annealing process in a vacuum permitted the formation of denser films and high oxidation states with a small number of oxygen vacancies in ZrO 2 films with a low leakage current [17]. Figure 4c,d shows the distribution of the representative parameters, such as the HRS, LRS, SET voltage, and RESET voltages.…”
Section: Resultsmentioning
confidence: 99%
“…ZrO 2 solution was synthesized by dissolving ZrCl 2 O•8H 2 O (Richjoint, Shanghai, China) in a 2-methoxyethanol (2ME) (Fuyu Fine Chemical, Tianjin, China) solvent. The solution was stirred at 300 r/min at room temperature for 2 h, and was then aged for at least one day [25]. The precursor solution was spin-coated on the indium tin oxide (ITO) substrate at 5000 rpm for 40 s. If multiple spin-coating was used, the wet films were pre-annealed at 300 • C for 5 min after each spin.…”
Section: Preparation Of Zro 2 Filmmentioning
confidence: 99%
“…Nowadays, a number of high-k metal-oxide dielectrics (such as Al 2 O 3 [7], ZrO 2 [8], HfO 2 [9], TiO 2 , Y 2 O 3 [10], Ta 2 O 5 and CeO 2 ) have been widely studied and used as an alternative to conventional SiO 2 dielectric layers (k = 3.9) with low leakage current density. Among these gate oxides, zirconium oxide (ZrO 2 ) is one of the attractive materials because of its excellent physical properties, for example, high dielectric constant (23)(24)(25)(26)(27)(28)(29), good thermal stability, wide band gap (5-7 eV), and large transparency in the visible and infrared ranges [11,12].…”
Section: Introductionmentioning
confidence: 99%